AB0111 THE COMPARISON OF SYNDECAN-4 LEVEL IN SERA, SYNOVIAL FLUID AND SYNOVIUM OF RHEUMATOID ARTHRITIS AND OSTEOARTHRITIS. (2nd June 2020) - Zhao, J.; Ye, X.; Zhang, Z.
Abstract : Background: Syndecan-4, one of the members of heparan sulphate proteoglycans (HSPGs), has been shown to be involved in regulating inflammatory responses, angiogenesis, and cell migration. Its role has been proved in animal arthritis models, however not clearly elucidated in rheumatoid arthritis (RA) patients Objectives: To investigate the role of Syndecan-4 in the pathogenesis of RA, by detecting Syndecan-4 expression in the serum, synovial fluid and synovium of RA patients and comparing with osteoarthritis (OA) patients Methods: The concentrations of syndecan-4 in sera and synovial fluid of RA and osteoarthritis (OA) patients were detected by ELISA. The expression of syndecan-4 in synovium of RA and OA patients was detected by immunohistochemistry. In another cohort of 60 RA patients, the association analysis was performed. All the RA patients were with disease duration more than 6 months and with DAS28-CRP>3.2 although after csDMARDs (including MTX and/or leflunomide) treatment for more than 3 months. The RA patients were treated with tumour necrosis factor α (TNFα) inhibitor (TNFi) and MTX 10mg per week for 12 weeks. The correlations between sera Syndecan-4 and disease activity of RA as well as therapeutic response to TNFi were analyzed. Results: The serum Syndedcan-4 level of RA patients [637.1 (483.6-1069.6) pg/mL] was significantly higher than that of OA patients [345.0 (287.9-421.1) pg/mL] and healthy controls [195.6 (165.0-225.2) pg/mL](P<0.001, P<0.001, respectively). The serum concentration of Syndecan-4 is also higher in OA patients than that in healthy controls (P<0.001). It was also higher in RF-positive RA patients than in RF-negative ones [603.0 (100.0-8879.1) pg/mL vs 460.3 (178.7-2468.9) pg/mL, (p=0.026)]. The Syndedcan-4 level in synovial fluid and synovia were comparable between RA and OA patients. No correlation was found between serum Syndedcan-4 and disease activity of RA. TNFi treatment did not change the serum Syndecan-4 level significantly. The baseline serum Syndecan-4 did not show predictive value for TNFi response. Conclusion: Syndecan-4 can be expressed in the synovia of RA and OA patients. The serum Syndecan-4 is higher in RA patients than in OA patients and healthy controls, and significantly higher in sero-positive RA patients than in sero-negative ones. Syndecan-4 may participate in the pathogenesis of RA. References: [1]Leonova EI, Galzitskaya OV. Role of Syndecans in Lipid Metabolism and Human Diseases. Adv Exp Med Biol, 2015, 855: 241-58. [2]Xie J, Wang J, Li R, Dai Q, Yong Y, Zong B, et al. Syndecan-4 over-expression preserves cardiac function in a rat model of myocardial infarction. J Mol Cell Cardiol 2012; 53: 250-8. [3]Strand ME, Aronsen JM, Braathen B, Sjaastad I, Kvaløy H, Tønnessen T, et al. Shedding of syndecan-4 promotes immune cell recruitment and mitigates cardiac dysfunction after lipopolysaccharide challenge in mice. J Mol Cell Cardiol. 2015;88:133-44. [4]Endo T, Ito K, Morimoto J, Kanayama M, Ota D, Ikesue M, et al. Syndecan 4 Regulation of the Development of Autoimmune Arthritis in Mice by Modulating B Cell Migration and Germinal Center Formation. Arthritis Rheumatol. 2015; 67:2512-22. Disclosure of Interests: None declared